2013
DOI: 10.1002/path.4286
|View full text |Cite
|
Sign up to set email alerts
|

Resistin derived from diabetic perivascular adipose tissue up‐regulates vascular expression of osteopontin via the AP‐1 signalling pathway

Abstract: Perivascular adipose tissue (PVAT) is implicated in the development of vascular diseases; however, the roles of PVAT on OPN expression in diabetic vasculature remain to be determined. This study investigated the role of adipokines derived from diabetic PVAT in regulating the vascular expression of OPN and explored the mechanisms involved. Aortic sections of ob/ob and high-fat diet (HFD)-induced obese (DIO) mice showed an increased expression of OPN, which was paralleled by increased amounts of PVAT characteriz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 42 publications
0
30
0
Order By: Relevance
“…Importantly, these attributes of hemin were accompanied by the restoration of adipocyte morphology and improved adipocyte function as evidenced by increased adiponectin levels. Given that hypertriglyceridemia, hypercholesteromia, and excessive pericardial adiposity are major pathophysiological causes of heart failure and related cardiac complications, 8,[43][44][45][46] the suppression of hypertriglyceridemia, hypercholesteromia, and pericardial adiposity in hemin-treated ZFs, and the corresponding decline of adipocyte hypertrophy, TGF-b, osteopontin, pro-inflammatory macrophage M1 phenotype, TNF-a, IL-6, IL-1b, and 8-isoprostane, [22][23][24][25][26][27][28][29][30][31]54,[60][61][62][63] which were associated with the potentiation of the anti-inflammatory macrophage M2 phenotype, proteins of regeneration such as beta-catenin, Oct3/4, and pax2 [32][33][34] are among the multifaceted mechanisms by which the HO system restores adipocyte morphology and improved adipocyte function. Moreover, the effect of the HO system on the expression of proteins of regeneration such as Oct3/4 and pax2 is a novel mechanism unveiled by this study through which hemin may restore adipocyte morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, these attributes of hemin were accompanied by the restoration of adipocyte morphology and improved adipocyte function as evidenced by increased adiponectin levels. Given that hypertriglyceridemia, hypercholesteromia, and excessive pericardial adiposity are major pathophysiological causes of heart failure and related cardiac complications, 8,[43][44][45][46] the suppression of hypertriglyceridemia, hypercholesteromia, and pericardial adiposity in hemin-treated ZFs, and the corresponding decline of adipocyte hypertrophy, TGF-b, osteopontin, pro-inflammatory macrophage M1 phenotype, TNF-a, IL-6, IL-1b, and 8-isoprostane, [22][23][24][25][26][27][28][29][30][31]54,[60][61][62][63] which were associated with the potentiation of the anti-inflammatory macrophage M2 phenotype, proteins of regeneration such as beta-catenin, Oct3/4, and pax2 [32][33][34] are among the multifaceted mechanisms by which the HO system restores adipocyte morphology and improved adipocyte function. Moreover, the effect of the HO system on the expression of proteins of regeneration such as Oct3/4 and pax2 is a novel mechanism unveiled by this study through which hemin may restore adipocyte morphology and function.…”
Section: Discussionmentioning
confidence: 99%
“…15,41 Plasma OPN levels are increased with hypertension in humans 21 and additional studies describe a potentially causal role for OPN in a variety of cardiovascular disease pathologies including atherosclerosis, 8 restenosis, 8 aneurysm formation, 5 myocardial infarction. 9 diabetic vascular disease 27 and vascular calcification. 31,32 …”
Section: Discussionmentioning
confidence: 99%
“…Resistin, discovered in 2001, was proposed as a potential link between obesity and diabetes (Steppan et al, ). It was found to be secreted by adipose tissue, macrophages, and other cell types (Jung et al, ; Calabrò et al, ; Park et al, ). However, in addition to its regulating role in insulin resistance and diabetes, several demonstrations reported that resistin was also involved in the pathological processes of atherosclerosis or cardiovascular diseases, including endothelial dysfunction and inflammation, thrombosis, and smooth muscle cell dysfunction (Jung et al, ; Cho et al, ; Jamaluddin et al, ).…”
Section: Discussionmentioning
confidence: 99%